Политическое в социальном: двойственность конструирования субъектности - Чикишев, Никита; Чикішев, Нікіта; Chykyshev, Nykyta; Капнинова, Марина; Капнінова, Марина; Kapnynova, Maryna (My University, 2016)
В современной Украине функционирует ряд общественных движений различного толка (ЛГБТ-сообщества, феминистские и пр.), которые оказывают значительное влияние на социально-политический климат в стране. Вопреки тому, что одним из главных критериев классификации организации как общественной является её внеполитичность, отдельные проявления активности вышеупомянутых организаций имеют политический характер. Такая двойственность создаёт ряд преград для изучения деятельности общественных организаций в рамках социологии. В связи с этим возникает необходимость выработки критериев классификации действий как политических / внеполитических, которые на данный момент не сформулированы в силу недостаточной разработанности и дискуссионности темы. У сучасній Україні функціонує низка громадських рухів різного напряму (ЛГБТ-спільноти, феміністські та ін.). Незважаючи на те, що один із головних критеріїв класифікації організації як громадської є її позаполітичність, окремі прояви активності вищезазначених організацій мають політичний характер. Така двоїстість створює низку перешкод для вивчення діяльності громадських організацій у межах соціології. У зв’язку з цим постає потреба вироблення критеріїв класифікації дій як політичних / позаполітичних, які на сьогодні не сформульовано внаслідок недостатньої розробленості та теми її дискусійного характеру. Study of the civil society gets a great importance in conditions of political instability. We face the necessity of exact definition of the origin of the different phenomena and processes during the research. The relevance is caused by the fact that today a number of facts and processes are deliberately labeled as non-political, despite of being inherently political, as some social movements like LGBT, feminists etc. The duality that was previously mentioned creates a number of barriers for study the activity of public organizations in sociology because of the uncertainty at the methodological level. In this regard, there is a necessity of the analyze of the activity of public organizations and development criteria for the classification of actions as a political or non-political. Nowadays they still haven’t been formulated yet because of novelty and argumentativeness of the topic of study.
Political in Social: Duality of Subjectivity's Constructing
Keywords: либерализм; глобализация; общественные организации; капитализм; субъектность; глобалізація; лібералізм; громадські організації; капіталізм; субʼєктність; globalization; civil society’s organizations; liberalism; capitalism; subjectivity